(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Central serous chorioretinopathy causes recurrences in 20–50 % of cases and becomes prolonged in 5–10 % of cases that often leads to visual acuity loss. The frequency of Helicobacter Pylory infection among patients with central serous chorioretinopathy is 39.7–86.2 % and exceeds that in general population. Purpose of the work was to determine the clinical efficacy of Helicobacter Pylory infection eradication in treatment of patients with chronic form of central serous chorioretinopathy. Materials and methods. 15 patients with primary chronic form and 36 patients with secondary chronic form of central serous chorioretinopathy participated in this study. Patients were divided into a main group (who were treated with omeprazol 40 mg, claritromycin 1000 mg, amoxicillin 2000 mg in a day for 7–10 days) and a control group (who were not treated). Results. In primary chronic form of the central serous chorioretinopathy using Helicobacter Pylory infection eradication in treatment of Hb-positive patients led to increasing positive dynamics with complete resorption of the subretinal fluid in 89 % of patients and improvement of distant prognosis after 2 years: visual acuity increased 1.2 times, decrease of scotoma frequency 1.8 times and scotoma size 3.9 times, decrease of metamorphopsia frequency 2.3 times and color pathology 2.3 times; statistically significant positive dynamics with complete resorption of the subretinal fluid was marked after 6 months in 89 % of patients. Using Helicobacter Pylory infection eradication in treatment of Hb-positive patients in case of secondary chronic form of the central serous chorioretinopathy led to decrease in recurrence frequency by 75 % and improvement of distant prognosis in 2 years: visual acuity increased 1.3 times, decrease of scotoma frequency 1.6 times and scotoma size 1.9 times, decrease of metamorphopsia frequency 1.4 times and color pathology 1.3 times; statistically significant positive dynamics with complete resorption of the subretinal fluid was marked after 6 months in all patients. Conclusions. Helicobacter Pylory infection eradication is effective in treatment of patients with chronic form of central serous chorioretinopathy.